Better Together: a Complementary Approach to Civil Judicial Remedies in Business and Human Rights - Aleydis Nissen (Penn State Law Review, 2018)
Effective civil judicial remedies are often inaccessible to victims of transnational corporations (TNCs) from economically developed states that operate in developing or emerging states. The general consensus is that local capacity development is the most practical solution. The alternative solution – opening the doors of courts to victims in other states (including TNC home states) – is often said to be illusory. One invited speaker at the CESCR's 2017 Discussion Day on business and human rights went as far as stating that extraterritorial remedies would only result in victims' disappointment. There is, however, an inconsistency in this argument. Extraterritorial remedies are still important to deal with current issues. This article weighs up the arguments and makes the case for a mixed approach consisting of both local and extraterritorial capacity development.
Keywords: H73; K33; K41; K42; 330; business and human rights; remediation; access to justice